Gender‐Related Mortality and In‐Hospital Complications Following ST‐Segment Elevation Myocardial Infarction: Data From a Primary Percutaneous Coronary Intervention Cohort. Issue 3 (27th February 2015) - Laufer‐Perl, Michal; Shacham, Yacov; Letourneau‐Shesaf, Sivan; Priesler, Ofir; Keren, Gad; Roth, Arie; Steinvil, Arie
ABSTRACT: Background: The increased mortality related to female gender in ST‐segment elevation myocardial infarction (STEMI) patients treated with primary percutaneous coronary intervention (PPCI) has been reported from various patient cohorts and treatment strategies with controversial results. In the present work, we evaluated the impact of female gender on mortality and in‐hospital complications among a specific subset of consecutive STEMI patients managed solely by PPCI. Hypothesis: Female gender is not an independent predicor for mortality among STEMI patients. Methods: We performed a retrospective, single‐center observational study that included 1346 consecutive STEMI patients undergoing PPCI, of which 1075 (80%) were male. Patient's records were evaluated for 30‐day mortality, in‐hospital complications, and long‐term mortality over a mean period of 2.7 ± 1.6 years. Results: Compared with males, females were older (69 ± 13 vs 60 ± 13 years, P < 0.001), had a significantly higher rate of baseline risk factors, and had prolonged symptom duration (460 ± 815 minutes vs 367 ± 596 minutes, P = 0.03). Females suffered from more in‐hospital complications and had higher 30‐day mortality (5% vs 2%, P = 0.008) as well as higher overall mortality (12.5% vs 6%, P < 0.001). In spite of the significant mortality risk in unadjusted models, a multivariate adjusted Cox regression model did not demonstrate that female gender was an independent predictor for mortality among STEMI patients. Conclusions: Among patients with STEMI treated by PPCI, female gender is associated with a higher 30‐day mortality and complications rates compared to males. Following multivariate analysis, female gender was not a significant predictor of long‐term death following STEMI.